The combination of anti-KIR monoclonal antibodies with anti-PD-1/PD-L1 monoclonal antibodies could be a critical breakthrough in overcoming tumor immune escape in NSCLC - He YY; Liu ST; Mattei J; Bunn Jr PA; Zhou CC; Chan D (Drug Design, Development and Therapy, 2018)
Yayi He,1,2,* Sangtian Liu,1,* Jane Mattei,3 Paul A Bunn Jr,2 Caicun Zhou,1 Daniel Chan2 1Department of Medical Oncology, Shanghai Pulmonary Hospital, Tongji University Medical School Cancer Institute, Tongji University School of Medicine, Shanghai, China; 2Division of Medical Oncology, Department of Medicine, University of Colorado Anschutz Medical Campus, Aurora, CO, USA; 3Oncology Department, Moinhos de Vento Hospital, Porto Alegre, Brazil *These authors contributed equally to this work Background: The anti-programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) monoclonal antibody has a good effect in the treatment of non-small cell lung cancer (NSCLC), but not all PD-1/PD-L1 positive patients can get benefit from it. Compensatory expression of other immune checkpoints may be correlated with the poor efficacy of anti-PD-1/PD-L1 monoclonal antibodies. The inhibitory human leukocyte antigen (HLA)/killer cell Ig-like receptor (KIR) can effectively block the killing effect of natural killer (NK) cells on tumors. Our previous studies have confirmed that high expression of KIR was correlated with poor prognosis of NSCLC. Inhibitory KIR expression was positively correlated with the expression of PD-1. Methods: The expressions of KIR 2D (L1, L3, L4, S4) (BC032422/ADQ31987/NP_002246/NP_036446, Abcam) and PD-1 (NAT 105, Cell marque) proteins was assessed by immunohistochemistry. Results: The expression of inhibitory KIR in tumor cells or tumor infiltrating lymphocytes (TILs) is associated with PD-1 expression. Among PD-1 positive patients, 76.3% were KIR 2D (L1, L3, L4, S4) positive on tumor cells, and 74.6% were KIR 2D (L1, L3, L4, S4) positive on TILs. We compared the expression of inhibitory KIR before and after treatment with nivolumab in 11 patients with NSCLC. We found that five (45.5%) patients had positive expression of inhibitory KIR in tumor tissue after being treated with anti-PD-1 monoclonal antibodies, two of whom exhibited a significant increase in expression of inhibitory KIR, and three showed no change. Conclusions: PD-1 expression was correlated with KIR 2D (L1, L3, L4, S4) on tumor cells or TILs. The resistance to anti-PD-1 monoclonal antibody treatment might be related to KIR. The inhibitory HLA/KIR could combine with the PD-1/PD-L1 signaling pathway negatively regulating NSCLC tumor immunity. Keywords: non-small cell lung cancer, immune therapy, HLA/KIR, PD-1/PD-L1, tumor immune escape